2016
DOI: 10.1016/j.tiv.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium mycotoxin enniatin B: Cytotoxic effects and changes in gene expression profile

Abstract: The mycotoxin enniatin B, a cyclic hexadepsipeptide produced by the plant pathogen Fusarium, is prevalent in grains and grain-based products in different geographical areas. Although enniatins have not been associated with toxic outbreaks, they have caused toxicity in vitro in several cell lines. In this study, the cytotoxic effects of enniatin B were assessed in relation to cellular energy metabolism, cell proliferation, and the induction of apoptosis in Balb 3T3 and HepG2 cells. The mechanism of toxicity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Juan-García et al ( 72 ) found that both ENN B and ENN A (1.5 and 3.0 µM) caused apoptosis in HepG2 cells, after 48 h of exposure, identifying ENN B more toxic than ENN A. Necrotic pathway was not observed. Similar results were obtained in mouse embryo fibroblast (Balb 3T3) cells (from 11 to 45 µM) ( 13 ), in murine monocyte (RAW 267.4) macrophages ( 35 ) and in human adrenocortical carcinoma cell line H295R ( 36 ).…”
Section: Toxicity Of Enn Bsupporting
confidence: 79%
See 2 more Smart Citations
“…Juan-García et al ( 72 ) found that both ENN B and ENN A (1.5 and 3.0 µM) caused apoptosis in HepG2 cells, after 48 h of exposure, identifying ENN B more toxic than ENN A. Necrotic pathway was not observed. Similar results were obtained in mouse embryo fibroblast (Balb 3T3) cells (from 11 to 45 µM) ( 13 ), in murine monocyte (RAW 267.4) macrophages ( 35 ) and in human adrenocortical carcinoma cell line H295R ( 36 ).…”
Section: Toxicity Of Enn Bsupporting
confidence: 79%
“…Enniatin B alone and in mixture with other ENNs induced apoptosis in several cell lines with nuclear fragmentation and apoptotic body formation ( 13 , 14 , 16 , 33 35 , 68 , 69 , 72 ). Moreover, the necrotic cell death has been also reported ( 10 , 16 , 35 ).…”
Section: Toxicity Of Enn Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive cytotoxic effects have already been reported in the presence of two or more mycotoxins (Fernandez-Blanco et al 2018;Zhou et al 2017). Similarly enniatin B has demonstrated adverse effects and changes in gene expression over different cell lines (Jonsson et al 2016;Manyes et al 2018).…”
Section: Mycotoxin Co-occurrencementioning
confidence: 93%
“…Negligible carry-over rates (0.0075% and 0%–0.0017%) were observed in cow milk after DON (2.62–5.24 mg/Kg) and ZON (0.33–0.66 mg/Kg) contaminated feed administration [ 24 ]. Due to the lipophilic nature of some mycotoxins, such as ENs and BEA, detectable concentrations were recovered from broiler and mice organs and tissues [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%